2021
DOI: 10.17679/inuefd.905569
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Relationship between Parents' Awareness of Digital Parenting and the Effects of Digital Games on Their Children

Abstract: With the changing living conditions and developing technology, digital parenting has become a noteworthy concept. Opening their eyes in a digital world, children have started to meet their needs such as games with digital games. The aim of this study is to examine parents' digital awareness levels and their views on the effects of digital games at an early age in terms of demographic variables. The quantitative research method was adopted in the study, and the model of the research is the factorial pattern, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…It should be noted that digital parenting does not mean parents play more digital games, but to provide them with an idea of the risks and gains they may face in digital games. In addition, parents need to develop a collaborative approach towards their children, so they will spend time playing with their children to improve their digital literacy, rather than limiting the children to poor outcomes of digital games (Akkaya et al, 2021;Bourgonjon, Valcke, Soetaert, De Wever & Schellens, 2011). Although the study presents some important results, it should not be forgotten that the sample is limited in generalization and interpretation.…”
Section: Discussionmentioning
confidence: 95%
“…It should be noted that digital parenting does not mean parents play more digital games, but to provide them with an idea of the risks and gains they may face in digital games. In addition, parents need to develop a collaborative approach towards their children, so they will spend time playing with their children to improve their digital literacy, rather than limiting the children to poor outcomes of digital games (Akkaya et al, 2021;Bourgonjon, Valcke, Soetaert, De Wever & Schellens, 2011). Although the study presents some important results, it should not be forgotten that the sample is limited in generalization and interpretation.…”
Section: Discussionmentioning
confidence: 95%
“…Similar studies (Jafari, 2021) showed that mothers are more concerned about digital security and EU. Other studies also show that digital parenting awareness levels do not differ according to gender (Akkaya et al, 2021). Another study concluded that the levels of SNE and DN of female parents were lower than those of male parents, and their levels of EU and PR were higher than those of male parents (Manap, 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 96%
“…Parents with an only child use technology more efficiently and protect their children more against risks than the parents who have two, three and four or more children. It was determined that the level of PR of parents who have four or more children significantly differs from that of parents who have an only child (Akkaya et al, 2021). Haddon and Holloway (2018) determined in their research that parents who have a child aged 0-5 years are less concerned about the explicit content on digital tools since they must take care of the younger child at home.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The level of awareness of parents about the effects of digital games on their children at an early age differs significantly according to the age at which children start playing digital games and the type of game they prefer to play. The level of awareness of parents about the effects of digital games on their children at an early age differs significantly only in the social sub-dimension, according to the age at which children start playing digital games (Akkaya et al, 2021).…”
Section: Children and Digital Mediamentioning
confidence: 99%